Titanate supported cobalt catalysts for photochemical oxidation of phenol under visible light irradiations - Zhou, Guanliang; Sun, Hongqi; Wang, Shaobin; Ang, Ha Ming; Tade, Moses (Pergamon, 2011)
Three metal titanates, ZnTiO3 (Zn), FeTiO3 (Fe) and Bi4Ti3O12 (Bi), were employed to prepare supported cobalt catalysts for photocatalytic and photochemical oxidation of phenol with peroxymonosulphate (PMS) or peroxydisulphate (PDS) under visible light irradiations. It was found that the oxidation efficiencies varied greatly due to the different photochemical behaviours of various supports. Using PMS, both Co(5%)/Zn and Co(3%)/Bi achieved complete degradation of phenol in 120 min, as compared to 66.9% of phenol removal on Co(5%)/Fe in 150 min. However, those catalysts were found not efficient in activation of PDS. Co(5%)/Bi, as the best catalyst, provided only 66.9% of phenol degradation in 150 min. The effects of the supports were related to the varying photophysical properties and the interactions with loaded Co3O4. The stability of Co(5%)/Zn with PMS was further investigated and it was found that 85.4% of the activity could be retained in phenol degradation in the fourth run.